HOW IS THE ROLE OF BPRS INTERMEDIATION IN INDONESIA? ANALYSIS OF INTERNAL AND EXTERNAL FACTORS TOWARDS FINANCING - Ariyani, Diyah; Rahmayanti, Dini; Widyastuti, Emy; Arinta, Yusvita Nena; Saifudin, Saifudin; Nugraini, Cantika Tri Lestari; Kamalia, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to analyze the relationship between the efficiency of Sharia Rural Banks (BPRS) and financing for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research covers 165 BPRS across 34 provinces during the 2017–2022 period, using panel data sourced from BI, OJK, and BPS. The findings indicate that BPRS efficiency significantly affects MSME financing. These results highlight the need for both policymakers and BPRS management to consistently improve efficiency in order to expand financing capacity. Moreover, the role of the OJK in overseeing and supporting BPRS is considered crucial to ensure better intermediation performance in serving MSMEs.